A construção da identidade quilombola em Cruzeiro: saberes tradicionais, conflitos sociais e estratégias de resistência - Paula, Iarinma de Morais (2019)
In the aforementioned study, on the socio-environmental conflicts experienced in the so-called quilombola community of Cruzeiro, which is located in the Maranhão state, as well as the resistance strategies triggered by these social agents through conflicts, with a more focused approach to the processes that have occurred since 2009, which has usurped the right of use and permanence in the territory by the selfdefined. In the reflections raised I bring knowledge and practices inherent to the way of life that are intrinsically related to the construction of the quilombola identity and the struggle for the guarantee of the territory. It is evident in the description that these social agents endowed with self-consciousness, establish collective agreements and strategies that renew themselves from the lived experiences to construct a unit. Thus, the dispute is circumscribed by the multiple forms of use of territories and their resources and the way in which territory and resources are given meaning. The senses attributed by the self-defined ones that give symbolic value to the territory, have been undergoing systematic actions, making the territory and the natural resources targets of the privatist yearnings with the exploitation of resources and devastation for cattle ranch production. In this sense, the present work analyzes the disputes that are circumscribed in a field for the legitimation of territorial recognition, considering that the reflections were possible through the network of relations built with the social agents of the quilombola community of Cruzeiro.